OracleTrust: A dual-layer provenance-based signature verification scheme for preventing transaction malleability in blockchain - Muhammad Rashid Majeed; Peiyun Zhang; Zeeshan Raza; Thoraya N. Alharthi; Ilyas Khan (PLoS ONE, 2026)
Decentralized oracle networks pose significant security risks to blockchain systems due to transaction malleability, which can lead to double-spending and integrity issues. While existing solutions such as DAON, SegWit, and SecPLF improve specific aspects of security, they do not address Oracle-driven transaction malleability on a transaction level. DAON focuses on decentralized oracle consensus and reputation mechanisms, but it does not support the cryptographic binding of Oracle metadata to transactions. SegWit reduces signature malleability at the Bitcoin protocol level, but it does not protect the integrity of Oracle-fed data or require validation before transactions are added to the blockchain. SecPLF protects loanable-fund protocols from Oracle manipulation, but it lacks a comprehensive transaction-level solution to prevent Oracle-driven malleability. OracleTrust, on the other hand, uses a dual-layer scheme to bind Oracle metadata and signatures to transactions via provenance tracking and a smart contract validation layer. The first layer encodes transactions into verifiable provenance records, and the second layer dynamically verifies these records with salted Keccak hashing and ECDSA recovery to bind the Oracle signature. A time-constrained commit-reveal mechanism with penalty enforcement ensures that the data is tamper-resistant. OracleTrust outperforms existing solutions in detecting malleable transactions, reducing latency, and memory consumption. This demonstrates its superior robustness and efficiency in blockchain.